SLR1 inhibits MOC1 degradation to coordinate tiller number and plant height in rice - Zhigang Liao (Nature Portfolio, 2019)
Due to reduced gibberellin sensitivity, modern rice cultivars are shorter than traditional varieties but produce more tillers and have higher yields. Here Liao et al. show that gibberellin contributes to decreased tiller number by degrading the MOC1 protein that suppresses bud outgrowth.